Effects of empathy mapping and mini-simulation on second-year nursing students’ empathy and communication self-confidence: a quasi-experimental study - Hsiang-Ping Huang; Yun Tien; Yung-Chang Lin; I-Chen Yu; Nai-Hui Chien (BMC Medical Education)
Abstract Background Empathy and communication are critical abilities for nursing students, and in recent years, scenario-based teaching has played a crucial role in fostering empathy and professional skill development. However, novice nursing students in basic nursing education often lack prior experience in patient communication, making it challenging for them to prepare adequately for scenarios and effectively handle difficulties in real-life situations. This deficiency also hampers participants’ or observers’ ability to engage in deep reflection, feedback, and learning. Consequently, students frequently experience anxiety in patient communication, and the effectiveness of empathy building remains limited. The aim of the study was to use empathy mapping and mini-simulation in learning to enhance nursing students’ empathy and self-confidence in communication. Methods A prospective quasi-experimental research design was employed, targeting second-year students in the four-year nursing program at our institution, specifically in the Basic Nursing and Experimentation II class. The students were randomly divided into two groups: an experimental group and a control group, with a total of 98 students (52 in the experimental group and 46 in the control group). The experimental group received instruction using empathic communication digital materials and engaged in empathy mapping exercises, while the control group underwent conventional scenario-based teaching. Pre-test and post-test data were collected from both groups. Results A total of 98 students participated in the study, with 46 students in the control group and 52 students in the experimental group. The average age of the participants was 19.19 ± 0.53 years, with a predominance of females (82.7%). At the end of the semester, there was no significant difference in the average empathy levels between the two groups. However, the communication confidence levels of students in the control group (40.20 ± 6.54) were significantly lower than those in the experimental group (43.88 ± 6.35) (P = 0.006). Conclusions This teaching approach facilitated deeper and broader student learning, enhancing both empathy and communication confidence. The teaching materials developed in this study can be employed in future courses to teach empathy and patient communication effectively.